HIV-1 targeting of IFN regulatory factors. (December 2011) - Remoli, Anna Lisa; Marsili, Giulia; Sgarbanti, Marco; Perrotti, Edvige; Fragale, Alessandra; Orsatti, Roberto; Battistini, Angela
Pathogens such as HIV-1 that cause chronic infections are particularly capable at adapting to the host in a manner that ensures long-term residence, and have evolved numerous mechanisms to evade various aspects of the innate and adaptive immune response. One of these mechanisms is the targeting of members of the IFN regulatory factor family. IFN regulatory factors are transcription factors that are implicated in the regulation of a variety of biological processes, including IFN induction and immune cell activation of downstream responses triggered by Toll-like receptors and other pattern-recognition receptors. Here, we report the specific targeting by HIV-1 of this class of cellular transcription factors, and describe how HIV-1 both makes them harmless and hijacks them, profoundly affecting their activity and turning them to its own advantage in order to facilitate its replication, survival, evasion of immune responses and spread.